Bangabandhu as the eternal sovereign: on the construction of a civil religion. Issue 4 (2nd October 2022) - Ruud, Arild Engelsen
ABSTRACT: The omnipresence of his name and portrait in Bangladesh suggests that Father-of-the-nation Sheikh Mujibur Rahman – known as Bangabandhu – is more than just a national hero. He is subject of a secular deification that establishes him as the fountain of political authority and an embodiment of the sovereignty of the nation – the one without whom there can be no authority, no sovereignty, no nation. Historically he was the supreme leader of the national movement, the extraordinary individual who created the independent nation. In that founding moment a new political order was formed, an order consciously maintained by the political party he founded and by his daughter, the current prime minister. This paper addresses the secular deification of him and investigates its efficacy as fountain for national sovereignty and for the authority of the political order.